Vajdaság népességmozgása az utóbbi fél évszázadban - Gábrity Molnár, Irén (Közép-Európai Közlemények, 2008)
According to the census of 2002 there are 7,498,001 people in Serbia, somewhat less than according to the previous census of 1991. On average 96.7 people live per km2. The number of households has constantly increased, however, the number of inhabitants of the households has decreased. The average age of men is 38.9 years, and their estimated life-span is 69.9 years, while the average age of women is 41.1, and their estimated life-span is 75.2. The proportion of urban inhabitants has tripled for the last 50 years. The number of people living in Vojvodina has constantly risen between 1948 and 1981, however, since then this number stagnates. Today more than 2 million people live in Vojvodina. The number of autochthonous inhabitants has been gradually decreased. The population density increased during the last 11 years (especially in Bacska), although due to immigrants. There has been a serious change in demography as the result of wars on the Balkans. Data show grave emigrational and immigrational processes. Agenda: achievement oriented and operable infrastructure, regional developmental projects to be planned in order to decrease elite emigrations, co-operative cross-border partnerships – the rise of willingness to invest and found enterprises, the establishment of institutional nets e.g. the net of educational and cultural institutions, settlement partnerships – plan of the regional developmental strategy and cooperation (constant cross-boarder contact and communication of the experts, the facilitation of the EU accession.